The effects of the medium of instruction on science learning of Hong Kong secondary students - Yip, Din Yan (2003)
Starting from 1998, a new language policy on the medium of instruction for secondary schools is implemented in Hong Kong. The policy stipulates that only 25% of secondary schools, which take in students with better academic and language abilities, are allowed to use English, the students' second language, as the medium of instruction, and the others have to use Chinese, the native language, for instruction. The present research project is a longitudinal study that aims to explore the effects of this language policy on the science learning of the English-medium and Chinese-medium students in the first three years of secondary schooling. The learning outcomes of the two streams of students were assessed by science achievement tests and a questionnaire on students' self-concept in science. The results obtained show that the English-medium students were disadvantaged in science learning, as they had relatively lower achievement scores and lower self-concept in science than those who learned through Chinese. Based on the analysis of students' performance on the test items, their perception of classroom climate in science lessons and classroom observations, the negative effects of learning science through English can be related to the limited English proficiency of the immersion students and inadequate repertoire of instructional strategies used by the science teachers. These negative effects, however, tended to become reduced with increase in time of immersion, probably because the English-medium students had become more proficient in English language skills and more confident in learning through English. Recommendation on the implementation of the language policy and teacher education programmes are proposed to resolve the problems faced by the English-medium students.